Significance of English Literacy and Academic Performance of Medical Students in USIM - Sanip, Suhaila; Zulkifli, Noor Fadzilah (EDUCARE, 2011)
ABSTRACT: English had been thought as one of the determining factor of academic excellence in medical school as students with better command of English are thought to have better understanding of the subjects compared to students who have poor command of English. English literacy has also been thought to be correlated with academic performance in medical school. While a lot of researches had been conducted on the relationship of English language proficiency and academic performance among non-native English speakers in other countries. The study on Malaysian medical students regarding this issue is still limited. The study was conducted to look at the correlation of English literacy and academic performance of medical students in USIM (Universiti Sains Islam Malaysia or Islamic Science University of Malaysia). This is a retrospective observational study. The results for âEnglish for Medical Sciencesâ in Semester 4 was compared to the performance in Pathology course in the Second Professional Examination in Semester 6. A correlation study showed no correlation between the English literacy and the academic performance of the medical students with r = -0.027. Therefore, there is no significant correlation between the English literacy and the academic performance of the medical students in USIM. KEY WORDS: English literacy, academic performance, medical student of USIM, and English language proficiency.Â Â About the Authors: Dr. Suhaila Sanip is a Lecturer (Medical Education) at the Faculty of Medicine & Health Sciences USIM (Islamic Science University of Malaysia) and now as Deputy Dean (Student Development & Performance Management) at the Faculty of Medicine & Health Sciences USIM, 13th Floor, Menara B, Persiaran MPAJ, Jalan Pandan Utama, Pandan Indah, 55100 Kuala Lumpur, Malaysia; and Dr. Noor Fadzilah Zulkifli is Senior Lecturer (Pathology), Multidisciplinary Laboratory Coordinator, and Pathology Course Coordinator at the Faculty of Medicine & Health Sciences USIM. They can be reached at: suhaila.s@usim.edu.my and nfadzilahz@usim.edu.myHow to cite this article? Sanip, Suhaila & Noor Fadzilah Zulkifli. (2011). âSignificance of English Literacy and Academic Performance of Medical Students in USIMâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.93-98. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 17, 2011); Revised (July 19, 2011); and Published (August 17, 2011).